Does the source of remittance matter? Differentiated effects of earned and unearned remittances on agricultural productivity - Shankar Ghimire; Kul Prasad Kapri (Economies, 2020)
This paper analyzes the effect of earned and unearned remittances on agricultural productivity in Nepal. This approach differs from the existing practice of studying the impact of total remittances on socio-economic outcomes. In particular, we disaggregate total remittances into earned and unearned remittances, and isolate their impacts on productivity-an individual household's per labor-hour production of all agricultural output at the market value. Methodologically, we follow a three-stage least squares (3-SLS) approach to overcome the potential endogeneity concerns. We provide evidence that unearned remittances are more effective than earned remittances in increasing agricultural productivity. These results can be useful in understanding the migration-remittance-productivity nexus in Nepal as well as other similar socioeconomic societies from South Asia.
Keywords: O15; F24; Q10; 330; 3-SLS; agricultural productivity; earned remittance; migration; Nepal; unearned remittance